Pengaruh Penerapan Green Accounting Terhadap Kinerja Perusahaan (Studi Pada Perusahaan Peraih Penghargaan Industri Hijau Yang Listing Di BEI 2020-2022) - Putri, Citra Maylinnda; Utami, Endang Sri (CV. ITTC INDONESIA, 2024)
This study aims to assess the effect of green accounting implementation on the performance of award-winning companies in the green industry listed on the IDX from 2020 to 2022. This study applies a quantitative methodology making use of secondary data from the Indonesia Stock Exchange publication for 2020 to 2022. The study population consists of companies that receive the PROPER predicate, especially those in the Gold and Green categories. The sample was identified by means of a purposive sampling strategy, resulting in 13 selected organizations, with a research technique involving multiple linear regression analysis. The research findings confirm that environmental spending has no impact on the company performance. This is because profit-oriented companies will take into account all expenses, including environmental expenses that reduce profit margins. Some companies categorize environmental costs as administrative and general costs, while others classify them as voluntary costs in their annual reports. Environmental performance positively affects company performance. Environmental performance (PROPER) effectively attracts stakeholders to invest in the organization. Companies that demonstrate strong environmental performance will receive positive responses from investors and stakeholders, thereby contributing to long-term revenue growth.